Legal analysis of the imbalance of wages between recruited workers and employees regarding minimum wages (decision number 99/Pdt.Sus-PHI/2024/PN Mdn) - Hetben Ricky Simangunsong; Aldi Subhan Lubis (Privietlab, 2025)
The wage disparity between recruited workers and assigned employees who bear equivalent workloads and responsibilities represents a serious issue in industrial relations in Indonesia. Recruitment workers often receive wages below the City Minimum Wage and experience discrimination in the provision of allowances and other normative rights, as occurred in the case of PT. Prima Multi Terminal. In this case, recruitment workers received Merit Salaries below the 2024 Medan City Minimum Wage, as well as unequal position allowances and leave entitlements compared to assigned employees, despite performing the same job functions. This condition contradicts the principle of justice and the principle of non-discrimination as stated in Article 6 of Law Number 13 of 2003 concerning Manpower and the provisions in Government Regulation Number 36 of 2021 in conjunction with Government Regulation Number 51 of 2023 concerning wages. This study aims to analyze the form of legal protection for recruitment workers who experience wage imbalance based on Decision No. 99/Pdt. Sus-PHI/2024/PN Mdn. The research method used was the normative legal method through a literature study approach and juridical analysis of the court decision. The results showed that the court partially granted the lawsuit and ordered the equalization of salaries and allowances. Therefore, the government needs to strengthen regulations, the labor inspection system, and improve legal education for workers.